Tinjauan Hukum Penghentian Polis Asuransi Terhadap Peserta Perspektif Peraturan Otoritas Jasa Keuangan Nomor 23/POJK.05/2015 dan Fatwa DSN-MUI Nomor 21/DSN-MUI/X/2001 (Studi di Takaful Keluarga Kota Malang) - Iva Maisaroh (Journal of Islamic Business Law, 2018)
This study aims to determine the termination of insurance policies against insurance participants conducted by the insurance company PT. Takaful Keluarga Malang city. The type of research used is empirical juridical research using the approach of Statue Approach and Conceptual Approach. Data sources are obtained from secondary and primary data sources. Data Collection of information obtained from interviews and documentation. From the results of research conducted shows that the termination of insurance policies against participants is done in writing by the insurance company PT. Takaful Keluarga Malang city because, the participants do not pay the insuransce premium in accordance with the deadline that has been agreed and there is no good faith to pay it in the grace period. When the participant's insurance policy is terminated by the insurance company, the participant can not make a claim to the company. For the return of premiums that have been paid by the insurance participants to the company, the terms of the contract used are the mudharabah (savings) and akar tabarru '(voluntary) contract. In the of Otoritas Jasa Keuangan Regulation Number 23 / POJK.05 / 2015 Article 27 explains that products that do not have the element of savings still get paid premium returns, this is different from the provisions of Fatwa DSN-MUI Number 21 / DSN-MUI / X / 2001 where in the insurance product that does not have elements of savings participants do not get a premium return